Eksistensi Gender Ditinjau Dari Sudut Pandang Al-Kitab (Studi Terhadap Agama Katolik) - Catur Widiat Moko (Intelektualita, 2018)
Gender is always being connected with equality and discrimination. Gender equality is about a balancing, harmony, and role equality and also a responsible among men and women. There are equality and also equity in having some rights, opportunities, cooperation, and relations among men and women. On the other hand, gender discrimination is a behaviour that tries to avoid, burden the equality of gender. This behaviour can cause an avoidance of the human right and the equality among men and women in many aspects, such as politics, economy, and socio-culture. Bible is the main source of every rule and Christian ethique. But the bible itself has patriarchy culture domination. Most of the scholar argued that the discrimination and injustice among men and women is a reflection of the culture. They can’t divide the gender concept that change and created in long term socio-culture process. The ideal status and role should be developed for the equality status among men and women. In some parts of the bible, there is role and status which are not ideal, or even show the discrimination to women, but that’s not the reason why we should avoid bible but we have to learn more about, what is the background and what is the purpose so we can get the best answer to solve all the gender problems.